(Words that the Al-Dane was silent about in Ottoman painting (In the Alifat - Harsha, Mohamed Salem (Arab Journal for Sciences and Research Publishing, 2021)
This research studies the expressions that Abu Amr Al-Dani kept silent about deleting the thousand through his persuasive book, and a statement of the ruling on drawing them, and comparing them with the texts of the rest of the scholars of drawing, and what was done on the work in the Qur’an of Libya by drawing the proximate, and other Qur’ans, with the preference of deletion or evidence in these Expressions, down to the most important results:The silent one has two parts: general and specific, the general is what all the scholars of drawing remain silent about, and the private is what one of the graphic scholars kept silent about and did not have a counterpart to him stipulatedThe ruling on the silent is based on odds, including a text from a graphic scholar, the existence of a disagreement in reading, and carrying on the analogues.Everything that Abu Amr Al-Dani kept silent about was worked to prove it in the Qur’an of Libya.
Keywords: Drawing; Silence; The Close One; The Masked One